Consumo alimentar: uma análise dos condicionantes comportamentais associados ao consumo de produtos ultraprocessados - Serafim, Monalisa da Costa (2017)
This paper goal was to identify which are the behavioral conditionings that influence the buying intention of ultraprocessed food and beverage, under the social marketing optics. The literature review made possible, through analysis of food consumption researches, to comprehend the factors and their relationship with the dimensions of interest in this paper (ultraprocessed buy-intention, attitude toward the ultraprocessed, subjective norm, self-efficacy and perceived control), resulting in nine hypotheses to empirical verification. The methodological procedures involved the creation of a questionnaire with scales that have been validated in other studies, being just adapted to this one. With the available data, we made an initial exploratory analysis, followed up by descriptive analysis, factor analysis and the use of structural equation modeling in order to verify the hypotheses. We found that convenience and sensorial appeal are the main factors that significantly contribute to a positive attitude regarding ultraprocessed food, and that they influence the buying intention of these products. This last one gets a strong negative influence from the self-efficacy construct, pointing out the importance of the individual's intern control to avoid the consumption of harmful to health food. Another important finding of the paper is the significantly interference of the facilitators construct to self-efficacy, showing that the impossibility to cook and the fact of eating by itself hinders the individual's control over its feeding choices.